Implementation of the Management Information System at the Community Learning Activity Center "Smart Bangun Negeri" - Sain, Sapiih (Journal of Psychology and Sustainable Education, 2024)
The management information system plays a role in supporting the implementation of activities at the Smart Bangun Negeri (SBN) Community Learning Activity Center (PKBM) Bogor Regency. This research aims to describe the implementation of the management information system in the PKBM SBN Bogor Regency. This research uses a qualitative method with a descriptive approach. Data collection uses interview, observation and documentation techniques. Analysis was carried out using a descriptive approach. The research results obtained show that the management information system in PKBM SBN is included in the quite optimal category. There are several obstacles faced by PKBM SBN. This will be corrected by the PKBM SBN management to optimize its role in society.